Healthcare professionals' preferences for surgery or primary endocrine therapy to treat older women with operable breast cancer. Issue 9 (September 2015) - Morgan, J.L.; Collins, K.; Robinson, T.G.; Cheung, K.-L.; Audisio, R.; Reed, M.W.; Wyld, L.
Abstract Introduction Primary endocrine therapy (PET) is an alternative treatment to surgery for oestrogen receptor (ER) positive operable breast cancer in older women. However, there is variable use of PET in the UK, with up to 40% of patients aged over 70 receiving PET instead of surgery in some regions. Treatment options offered to patients rely heavily on healthcare professional (HCP) assessment and opinion on which treatments are appropriate. Materials and methods This was a mixed methods study combining semi-structured interviews with HCPs working in high and low PET regions in the UK, followed by a postal questionnaire survey distributed via the Association of Breast Surgery (ABS). Results Thirty-four HCPs (20 breast surgeons; 13 nurse specialists; 1 geriatrician) were interviewed from 14 sites across the UK and 252/641 questionnaires returned (39%). There was an overriding view that PET is not suitable for patients under the age of 80 unless there are significant comorbidities. Opinion was split regarding the best way to treat patients with dementia. Patient preference was generally stated to be the most important factor when considering treatment, however only around a quarter 65/244 (26.6%) felt that all patients over the age of 70 should be offered PET as an alternative treatment option. Conclusions Opinions differ on the best way to treat women over 70 with operable breast cancer, especially if they have co-existing dementia, as well as whether they should be offered PET as a treatment option. This may be a significant cause of treatment variation in the UK.